Natural phytochemicals prevent side effects in BRCA-mutated ovarian cancer and PARP inhibitor treatment - Wang, Chuanlin; Gao, Pengning; Xu, Jiali; Liu, Shanling; Tian, Wenda; Liu, Jiayu; Zhou, Lan (Frontiers in Pharmacology, 2022)
Ovarian cancer is among the most common malignant tumors in gynecology and is characterized by insidious onset, poor differentiation, high malignancy, and a high recurrence rate. Numerous studies have shown that poly ADP-ribose polymerase（PARP） inhibitors can improve progression-free survival (PFS) in patients with BRCA-mutated ovarian cancer. With the widespread use of BRCA mutation and PARP inhibitor (PARPi) combination therapy, the side effects associated with BRCA mutation and PARPi have garnered attention worldwide. Mutations in the BRCA gene increase KEAP1-NRF2 ubiquitination and reduce Nrf2 content and cellular antioxidant capacity, which subsequently produces side effects such as cardiovascular endothelial damage and atherosclerosis. PARPi has hematologic toxicity, producing thrombocytopenia, fatigue, nausea, and vomiting. These side effects not only reduce patients’ quality of life, but also affect their survival. Studies have shown that natural phytochemicals, a class of compounds with antitumor potential, can effectively prevent and treat the side effects of chemotherapy. Herein, we reviewed the role of natural phytochemicals in disease prevention and treatment in recent years, including sulforaphane, lycopene, catechin, and curcumin, and found that these phytochemicals have significant alleviating effects on atherosclerosis, nausea, and vomiting. Moreover, these mechanisms of action significantly correlated with the side-effect-producing mechanisms of BRCA mutations and PARPi. In conclusion, natural phytochemicals may be effective in alleviating the side effects of BRCA mutant ovarian cancer cells and PARP inhibitors.